Counterfactual Modeling in Historical Reconstruction: El Lissitzky's Horizontal Skyscraper WB2. Issue 1 (2nd January 2022) - Johnson, Samuel; Dixit, Mitesh; Boyer, Lawry; Melville, Stephen
Abstract : In this project, three drawings for a horizontal skyscraper by El Lissitzky are analyzed and reconstructed using an iterative design process. The historical drawings serve as the basis of a series of models that attempt to visualize the architect's design process by focusing on gaps, interruptions, inconsistencies, and contradictions in the representational field. A coherent and integrated massing, structure, and materials can be reconstructed by selecting a stable set of elements from the drawings. Improbable geometries constructed based on other elements foreground the normative force of the design as an ideal object that the historical architect never produced. Thanks to a counterfactual model, this ideal object can be examined in relation to historical design methodologies.